Classification of Health Structural Indicators Using Scalogram Model in Golestan Province, Northern Iran - M Bahadori; L Shams; J Sadeghifar; P Hamouzadeh; M Nejati (Iranian Journal of Public Health, 2012)
Background: One of the main and basic pillars of health system promotion is the equitable distribution of health facilities in order to ensure fair access of people in the community to the health services. The goal of this study was to classify the health structural indicators in Golestan Province using Scalogram analysis model. Method: A descriptive study was conducted in 2010. Data related to indicators in 3 categories of institutional, human resources and rural health and their indicators were collected using statistical yearbook. Data analysis was done using SPSS software and scalogram analysis model. Results: There is large gap between health structural indicators in cities of Golestan Province. Aq Qala City with 97 score and Azad Shahr City with 41 score were the most and lowest scores respectively from enjoyment of health structural indicators. Generally, 18% of cities were in less developed level and only 27% of cities were developed level. Conclusion: To achieve a fair and balanced healthcare status in different provinces based on their state of development, plans should be arranged in order to reduce the gap in the access to healthcare facilities.